On the family Fissiphalliidae Martens, 1988, with descriptions of two new Amazonian species (Arachnida: Opiliones: Laniatores) - Tourinho, Ana Lúcia; González, Abel Pérez (Zootaxa, 2006)
Two new species of Brazilian Fissiphalliidae are described. Fissiphallius chicoi n. sp. from Pará State, Gurupá municipality, whitewater floodplains (várzea), and Fissiphallius tucupi n. sp. from Amazonas State, Castanho municipality (paleovárzea). The number of species for this family in the Amazon rainforest increases from one to three. The two new species are closely related to Fissiphallius martensi Pinto-da-Rocha, 2004 from Amazonas State, Manaus. Fissiphalliidae and Zalmoxidae show remarkable similarities in somatic and genital morphology. Fissiphalliidae is kept as a family on the basis of its particular shape of the stragulum, but this character should be tested in a phylogenetic framework. A future phylogenetic analysis should determine if Fissiphalliidae is in fact the sister group of Zalmoxidae, or just a junior synonym. A key for identification, a distribution map, and notes on the distribution of the six species of Fissiphalliidae and the biology of the Amazonian species are given.